Age and Sex Recognition of Speakers - Nataraja NP; Kushal Raj P (Journal of All India Institute of Speech and Hearing, 1970)
Studies have been conducted to identify speaker's age, Ptacek and Sander, (1966); Shipp and Hollien, (1969); Ryan and Burk, (1972):Burk, Hoyer, Fey and Charlip, (1975); Hartman and Danhauer, (1969); Sex(Schwartz, 1968); Schwartz and Rine (1968); Ingemann, (1968); Coleman, (1971: 1973a; 1976); Lass, Hughes, Bowyer, Waters and Bourne, (1976); Lass, Tecca, Mancuso and Black,  (1979c); Lass, Mertz and Kimmel, (1978); Lass, Almerino Jordon and Walsh, (1980d) race (Stroud, 1956; Hibler, 1960; Dickens and Sewyer,  1962; Larson and Larson,1966; Bryden, 1968; Alverenga, 1970; Abram, 1975; Lass et al,  1979c;  Lass, Mertz and Kimmel, 1978; Lass et al.,   1980d),  Socio-econcmic status (Harms, 1961; 1963), personality (Stagner, 1936; Eisenbeig and Zalowitz, 1938; Markel, Eisleer and Reese,1967),   specific identity   (McGehee, 1937; Pollack, Pickett and Sumby,  1954; Compton,  1963;  Voiers, 1964; Clarke Becker and  Nixon, 1966; Bricker and Pruzansky,1966; Holmgeen, 1967; Stevens, Williams, Carbonell and Woods, 1968; Clarke and Becker, 1969; Coleman, 1973b)  and facial features (Lass and Harvey, 1976).These studies have been considered to 'provide very useful information in a variety of future theoretical and applied areas of investi- gation' (Lass et al. 1980). For example,  the  information  from  such  studies will be useful in training listeners in recognizing various characteristics of speakers.